1986
DOI: 10.3109/10641968609046575
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory Blood Pressure in Children Followed for 3 Years: Influence of Sex and Family History of Hypertension

Abstract: In 100 children (63 boys and 37 girls) aged 11.3 +/- 0.6 years ambulatory blood pressure (BP) was recorded by a semi-automatic device (Remler) 9 times per year over a period of 3 years. A sex difference in systolic BP was noted from the age of 13 years on with boys having higher values by about 6 mmHg (p less than .05). This could not be explained by differences in weight. In boys parental hypertension was associated with higher systolic values independent on age (p less than .05). Genetic and hormonal factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Evidence from a number of sources has suggested that mechanisms of blood pressure homeostasis might be quite different for males and females (40,41). For example, in several models of hypertension, elevated blood pressure develops sooner and is more severe in males than females (42).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from a number of sources has suggested that mechanisms of blood pressure homeostasis might be quite different for males and females (40,41). For example, in several models of hypertension, elevated blood pressure develops sooner and is more severe in males than females (42).…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] The Hypertension in Pregnancy Offspring Study showed that mothers with gestational hypertension and with sustained postpartum hypertension (for 7-12 years following birth) have hypertensive children at greater frequency than mothers with gestational hypertension but no postpartum hypertension. 14 These findings strongly suggest that cardiovascular risk factors (CVRFs) could emerge before adolescence in offspring of hypertensive subjects.…”
mentioning
confidence: 99%
“…As with most measurements in pediatrics, normal values for ABPM must be adjusted for body size (as a surrogate for maturational age) 92 and gender. 106 Where sufficient data are available, evaluation specific for race or ethnic differences should be performed. 107,108 Unfortunately, only limited large population-based cross-sectional studies have been performed using ABPM in healthy children, and few have truly proportional representation across age, race, body size, and gender.…”
Section: Distribution Of Bp Values On the Basis Of Abpm Normative Datmentioning
confidence: 99%